Vem är den goda läraren? - Jonas Nordmark; Eva Bolander (Utbildning & Demokrati)
Who is the good teacher? Teacher ideals in sexuality education. This paper explores the construction of teacher ideals in the context of sexuality education – a curricular area marked by numerous, and often conflicting, expectations on the teachers responsible for teaching it. Using a curriculum theory approach, a thematic analysis of Swedish teacher guides on sexuality education from 1956 to 2014 was conducted. The study examines how these manuals shape conceptions of both the knowledge domain and teacher ideals. The findings identify four main teacher ideals across the guides, revealing a mix of divergent and recurring ideas about teachers’ roles, encompassing both personal and professional qualities. Notably, the teacher ideals in the earlier guides (from 1956 and 1977) are presented implicitly, while the 1995 guide explicitly outlines the attributes of a good teacher. The study suggests that shifts in teacher ideals may be linked to broader changes in the content focus of the guides, though this relationship must be understood within the often-fragile amalgamation of competing ideals.